PHENOLIC COMPOSITION, ANTIOXIDANT AND ANTIMICROBIAL ACTIVITIES OF ZIZYPHUS LOTUS L. AND RUTA CHALEPENSIS L. GROWING IN MASCARA (WESTERN ALGERIA) - Bekkar, Nour El Houda; Meddah, Boumediene; Cakmak, Yavuz Selim; Keskin, Bahadir (SLOVAK UNIV AGRICULTURE NITRA, 2021)
In this study, the phenolic composition, antioxidant and antimicrobial activities of Zizyphus lotus and Ruta chalepensis collected from Mascara-Western Algeria were investigated. The total phenolic, flavonoid and tannin contents in the methanolic (Me.E) and aqueous (Aq.E) extracts were measured using colorimetric methods. Polyphenolic profiles were analyzed by high performance liquid chromatography (HPLC), while the antioxidant effect was determined by DPPH* radical scavenging assays. The antimicrobial activity was estimated using agar disc diffusion and microdilution methods. The results showed that total phenolic compounds, flavonoids and tannins were significantly higher (p <0.05) in Z. lotus extracts when compared with R. chalepensis. The major phenolic compound detected in Z. lotus was benzoic acid (1333.59 mu g/g DE), while the hydroxybenzoic acid (56.60 mu g/g DE), chlorogenic acid (44.60 mu g/g DE), epicatechin (38.80 mu g/g DE), catechin (26.30 mu g/g DE) and gallic acid (13.22 mu g/g DE) were the major compounds in R. chalepensis. Both plants were determined to be effective antioxidants regarding their lower IC50 values of 0.146 mg/mL for Z. lotus Me.E and 0.206 mg/mL for R. chalepensis Aq. E. Results demonstrated that Me.E of Z. lotus and R. chalepensis were more active against S. enterica ssp arizonae, while the lowest minimum inhibitory concentration was recorded against H. alvei using Z. lotus aqueous extract (25 mg/mL). An important anti-Candida activity was also determined. These results suggest the most efficiency of both plants, in the treatment of various human infections, regarding their potential on bioactive molecules with antioxidant and antimicrobial activities.
Keywords: Zizyphus lotus; Ruta chalepensis; Western Algeria; Phenolic compounds; HPLC-DAD; Antioxidant; Antimicrobial; ESSENTIAL OILS; EXTRACTION; LEAVES; PLANTS; Food Science & Technology